Design of New Single-phase Multilevel Voltage Source Inverter - Rasoul Shalchi Alishah; Daryoosh Nazarpour; Seyyed Hossein Hosseini; Mehran Sabahi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
Multilevel inverters with more number of levels can produce high quality voltage waveforms. In this paper, a new single-phase structure for multilevel voltage source inverter is proposed which can generate a large number of levels with reduced number of IGBTs, gate driver circuits and diodes. Three algorithms for determination of dc voltage sources’ magnitudes are presented which provide odd and even levels at the output voltage waveform. A comparison is presented between proposed multilevel inverter and conventional cascade topology. The proposed topology is analyzed by the experimental and simulation results.DOI: http://dx.doi.org/10.11591/ijpeds.v5i1.6218